Effect of irrigation water salinity and its mode of application on garlic growth and production - Amorim, Júlio Roberto de Araújo; Fernandes, Pedro Dantas; Gheyi, Hans Raj; Azevedo, Norma César de (Pesquisa Agropecuaria Brasileira, 2002)
In Paraíba State, Brazil, garlic is usually irrigated by sprinkler system using waters of varying salt concentrations that may cause damage to plants. The present study was carried out under greenhouse conditions testing five levels of water salinity varying from 0.6 to 3.0 dS m-1 and two modes of water application, wetting or not plant leaves. The growth and development of plant was evaluated at 30, 60, 90 and 120 days after planting (DAP). Garlic plants are relatively tolerant to salinity at bulb formation stage and initial growth up to 30 days. During the final stage (90-120 DAP), wetting of leaves affected more the growth of aerial parts and the number of garlic cloves. The salinity levels started affecting aerial parts during the period of 30-60 days while the bulb was affected only between 60-90 DAP. The most sensitive phase of bulb growth to salinity was the last 30 days of crop cycle. The bulb ratio can not be utilized as a characteristic for evaluation of salinity tolerance in garlic.